Recurrence in the pharynx 11 years after a total laryngectomy - Drexler, Günther (Cirugía del Uruguay, 1982)
A 67 year old white male patient developed a second primary malignant neoplasm in the posterior wall of the pharynx, 11 years after total laryngectomy and radiation therapy (6.000 rads total tumor dose) for a supraglottic carcinoma. Surgery was performed with curative intent removiug the 5 x 2 cm lesion via a combined cervical and transolral approach. The defect was covered with a free skin graft. Normal pharyngeal function was restored 10 days postoperatively. The patient is remaining "cancer free" 1 and 1 /2 years after surgery. The author comments the poor prognosis of pharyngeal recurrences or second primary malingnancies developed in the area. These patients should be spared a long stay in the hospital and multiple surgical procedures. Continual exposure to carcinogenetic factors (cigarette) is stressed as an important factor in the developement of a second primary malignant neoplasm.